A randomized controlled trial of 5 daily sessions and continuous trial of 4 weekly sessions of repetitive transcranial magnetic stimulation for neuropathic pain. Issue 2 (February 2020) - Hosomi, Koichi; Sugiyama, Kenji; Nakamura, Yusaku; Shimokawa, Toshio; Oshino, Satoru; Goto, Yuko; Mano, Tomoo; Shimizu, Takeshi; Yanagisawa, Takufumi; Saitoh, Youichi
Abstract : Abstract: We conducted a multicenter, randomized, patient- and assessor-blinded, sham-controlled trial to investigate the efficacy of repetitive transcranial magnetic stimulation (rTMS) of the primary motor cortex (M1) in patients with neuropathic pain (NP). Patients were randomly assigned to receive 5 daily sessions of active or sham rTMS of M1 corresponding to the part of the body experiencing the worst pain (500 pulses per session at 5 Hz). Responders were invited to enroll in an open-label continuous trial involving 4 weekly sessions of active rTMS. The primary outcome was a mean decrease in a visual analogue scale of pain intensity (scaled 0-100 mm) measured daily during the daily sessions in an intention-to-treat population. Secondary outcomes were other pain scores, quality-of-life measures, and depression score. One hundred forty-four patients were assigned to the active or sham stimulation groups. The primary outcome, mean visual analogue scale decreases, was not significantly different ( P = 0.58) between the active stimulation group (mean, 8.0) and the sham group (9.2) during the daily sessions. The secondary outcomes were not significantly different between 2 groups. The patients enrolled in the continuous weekly rTMS achieved more pain relief in the active stimulation group compared with the sham ( P < 0.01). No serious adverse events were observed. Five daily sessions of rTMS with stimulus conditions used in this trial were ineffective in short-term pain relief in the whole study population with various NP. Long-term administration to the responders should be investigated for the clinical use of rTMS on NP in the future trials. Abstract : Supplemental Digital Content is Available in the Text.Five daily sessions of repetitive transcranial magnetic stimulation with stimulus conditions were ineffective in neuropathic pain relief. Long-term administration should be investigated for clinical use of repetitive transcranial magnetic stimulation in neuropathic pain.